Tingkat Pendapatan dan Kelayakan Usaha Tani Cabai Merah di Dusun Taeno Desa Rumahtiga Kota Ambon - Nova Fadersair; August E Pattiselanno; Jetter D Siwalette (Ideas Publishing, 2023)
Cayenne pepper is an important commodity that causes inflation in Ambon City. Inflation conditions occur because there are frequent price fluctuations due to fluctuations in the supply of these commodities. Therefore, this research aims to analyze the income level and feasibility of red chili farming in Taeno Hamlet, Rumahtiga Village, Ambon City. The results of the research concluded that the income of red chili farmers, the income of cayenne pepper farmers in Taeno Hamlet was obtained from a total income of Rp958,200,000,00 with an average of Rp23,955,000,00 minus total production costs of Rp219,995,000,00 with an average IDR 5,499,875,00 so that the income received by cayenne pepper farmers in Taeno Hamlet is IDR 738,205,000,00 with an average of IDR 18,455,125,00 per year. The Revenue Cost Ratio results show a ratio value of 4.36 which is obtained from total income divided by total production. Based on the results of the feasibility analysis of cayenne pepper farming, R/C. Thus, it can be concluded that cayenne pepper farming in Taeno Negeri Rumahtiga Hamlet, Teluk Ambon District is worth pursuing.